Complete PCB design using OrCAD capture and PCB editor - Mitzner, Kraig; Doe, Bob (Application engineer); Akulin, Alexander; Suponin, Anton; Muller, Dirk (Electrical engineer) (Academic Press, an imprint of Elsevier, 2019)
Complete PCB Design Using OrCAD Capture and PCB Editor, Second Edition, provides practical instruction on how to use the OrCAD design suite to design and manufacture printed circuit boards. Chapters cover how to Design a PCB using OrCAD Capture and OrCAD Layout, adding PSpice simulation capabilities to a design, how to develop custom schematic parts, how to create footprints and PSpice models, and how to perform documentation, simulation and board fabrication from the same schematic design. This book is suitable for both beginners and experienced designers, providing basic principles and the program's full capabilities for optimizing designs. Companion site https://www.elsevier.com/books-and-journals/book-companion/9780128176849 Presents a fully updated edition on OrCAD Capture, Version 17.2 Combines the theoretical and practical parts of PCB design Includes real-life design examples that show how and why designs work, providing a comprehensive toolset for understanding OrCAD software Provides the exact order in which a circuit and PCB are designed Introduces the IPC, JEDEC and IEEE standards relating to PCB design.